Implementation of village fund management among the Wajo Bugis ethnic, Indonesia - Mustaking, Mustaking; Iqbal, Andi Muh Baso; Daris, Lukman; Demmallino, Eymal B.; Ismail, Ahmad; Massiseng, Andi Nur Apung (ETNOSIA : Jurnal Etnografi Indonesia, 2023)
The village fund program is a government program to accelerate and equalize development in rural areas, oriented towards poverty alleviation in Indonesia. This research aims to describe the Village Fund Program policy implementation in Wajo Regency, South Sulawesi. The type of research used is qualitative. Data was collected through in-depth interviews with informants and observations in the research object area. The informants in this study were selected purposively and in snowball sampling. The novelty of this research is to examine the successful implementation of village fund program policies in Wajo Regency using a combination of Jones's theory and Edward's theory based on three pillars, namely (1) organizational pillar, (2) interpretation pillar, and (3) application pillar, which is connected to ethnic culture. Wajo bugis. The research results show that implementing the village fund program in Wajo Regency needs to run optimally. This is because the competency of individual program implementers needs to be improved. The regulations governing program policies open up opportunities for abuse. Institutionally, policy implementers need more time to be ready to run the program optimally because the readiness of the organizational infrastructure needs to be balanced.